Admixture composition, cement composition and method for producing same

The use of biomass combustion ash and limestone in a specific ratio within the cement composition addresses the challenge of maintaining fluidity in high temperature environments, while reducing environmental impact and preventing material separation.

JP7663397B2Active Publication Date: 2025-04-16MITSUBISHI UBE CEMENT CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021060000
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-04-16
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Cement compositions used in high temperature environments face challenges in maintaining fluidity due to hydration reactions, leading to reduced flowability over time, and the use of additives like water reducing agents can cause material separation.

Method used

A mixture composition containing biomass combustion ash with specific calcium oxide and chlorine content ranges, combined with limestone, is used to create a cement composition that exhibits moderate flowability in high temperature environments, while reducing environmental impact.

Benefits of technology

The proposed cement composition achieves moderate fluidity in high temperature environments, reduces environmental impact by utilizing waste materials, and maintains stability against material separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663397000001
    Figure 0007663397000001
  • Figure 0007663397000002
    Figure 0007663397000002
Patent Text Reader

Abstract

To provide a mixture composition capable of imparting fluidity to a cement composition under a high temperature environment.SOLUTION: One aspect of the present disclosure provides a mixture composition containing biomass combustion ash with a total calcium oxide content of 15 mass% or more, a free calcium oxide content of 0.60 mass% or more, and a chlorine content of 0.95 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to admixture compositions, as well as cement compositions and methods for making same. [Background technology]

[0002] In general, when cement is used in a high-temperature environment, the hydration reaction of the cement components is accelerated, causing a significant decrease in fluidity over time. To address this problem, large amounts of high-performance water-reducing agents, high-performance air-entraining water-reducing agents, hardening retarders, and the like are used as additives to maintain fluidity during the transportation of ready-mix concrete or during the construction of concrete, which requires a long time (for example, Patent Document 1).

[0003] Meanwhile, limestone is widely used as an admixture to be mixed with cement. In consideration of the environment, waste materials and industrial by-products are used as admixtures instead of limestone to reduce the amount of limestone, which is a natural resource, used. For example, industrial by-products such as blast furnace slag, coal ash, and silica fume are used as small amounts of admixture components added to ordinary Portland cement. In addition, Patent Document 2 discloses a mortar fluidizing additive containing the above admixture or a ceramic fine powder, a highly dispersible water reducing agent, and a lithium composition, and a method for producing mortar using the above mortar fluidizing additive.

[0004] However, if waste materials and industrial by-products other than the above-mentioned blast furnace slag, coal ash, and silica fume could be used as cement admixtures, it would be possible to further reduce the environmental load and contribute to the creation of a recycling-oriented society. Examples of inorganic powders that have not been used much as admixtures so far include combustion ash generated when burning biomass fuel, biomass waste, and general garbage.

[0005] In particular, in recent years, the use of biomass fuel as a renewable energy source has been increasing. For example, in Patent Document 3, wood biomass, paper sludge, etc. are used as biomass fuel to reduce the environmental load. Ash after combustion (biomass combustion ash) discharged from the use of such biomass fuel is discharged in large amounts as an industrial by-product, and there is a demand for its effective use. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2009-021901 A [Patent Document 2] JP 2006-069854 A [Patent Document 3] JP 2017-122550 A Summary of the Invention [Problem to be solved by the invention]

[0007] When an admixture such as a water reducing agent is used when mixing a cement composition under a high temperature environment, problems may occur such that the expected fluidity cannot be ensured due to interactions with cement clinker, gypsum, and other admixtures, or the fluidity may become too high over a long period of time, causing material separation.

[0008] The present disclosure aims to provide an admixture composition capable of imparting appropriate fluidity to a cement composition in a high-temperature environment. The present disclosure also aims to provide a cement composition that contains the admixture composition, contributes to reducing environmental load, and exhibits appropriate fluidity in a high-temperature environment, and a method for producing the same. [Means for solving the problem]

[0009] One aspect of the present disclosure provides an admixture composition comprising biomass combustion ash having a total calcium oxide content of 15% by weight or more, a free calcium oxide content of 0.60% by weight or more, and a chlorine content of 0.95% by weight or less.

[0010] The biomass combustion ash has a total calcium oxide content and a free calcium oxide content in the calcium oxide that are within a specified range, and also has a chlorine content that is within a specified range, so that it is possible to impart appropriate fluidity to the cement composition in a high temperature environment.

[0011] The zinc content in the biomass combustion ash may be 0.25 mass % or more.

[0012] The above biomass combustion ash has a Blaine specific surface area of ​​7000 cm 2 / g or more.

[0013] The admixture composition may further contain limestone, and the content of the biomass combustion ash may be 0.1 to 55.0 mass % based on the total amount of the biomass combustion ash and the limestone.

[0014] One aspect of the present disclosure provides a cement composition comprising cement clinker, gypsum, and the above-mentioned admixture composition, wherein the content of the admixture composition is more than 5.0 mass% and not more than 20.0 mass%.

[0015] The above cement composition contains a relatively large amount of the admixture composition containing the above biomass combustion ash, while the content of the above admixture composition is within a specified range, thereby contributing to reducing the environmental load and exhibiting appropriate fluidity in a high-temperature environment.

[0016] In the cement composition, the hemihydration rate of the gypsum may be 40 to 100 mass %.

[0017] The cement clinker may have a C3S content of 40.0 to 70.0 mass%, a C2S content of 5.0 to 40.0 mass%, a C3A content of 7.0 to 13.0 mass%, and a C4AF content of 7.0 to 13.0 mass%.

[0018] The cement composition may have an SO3 content of 1.0 to 3.5 mass %.

[0019] The cement composition may further contain at least one admixture selected from the group consisting of a water reducing agent, an air-entraining water reducing agent, a high-performance water reducing agent, a high-performance air-entraining water reducing agent, and a superplasticizer.

[0020] The admixture may contain a polycarboxylic acid compound.

[0021] One aspect of the present disclosure provides a method for producing a cement composition, comprising: a mixing step of mixing raw materials including cement clinker, gypsum, and the above-mentioned admixture composition such that the content of the admixture composition is more than 5.0 mass% and not more than 20.0 mass%.

[0022] The method for producing the cement composition uses the above-mentioned admixture composition as an admixture, and mixes a relatively large amount of the biomass combustion ash as an admixture while mixing so that the content of the admixture composition is within a predetermined range, thereby producing a cement composition that contributes to reducing the environmental load and can exhibit appropriate fluidity in a high-temperature environment. Effect of the Invention

[0023] According to the present disclosure, it is possible to provide an admixture composition capable of imparting appropriate fluidity to a cement composition in a high-temperature environment. According to the present disclosure, it is also possible to provide a cement composition that contains the above-mentioned admixture composition, contributes to reducing environmental load, and exhibits appropriate fluidity in a high-temperature environment, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. In the following description, when it is written "X to Y" (X and Y are arbitrary numbers), it means "X or more and Y or less" unless otherwise specified.

[0025] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.

[0026] One embodiment of the cement composition contains a mixture composition including cement clinker, gypsum, and biomass combustion ash. The biomass combustion ash in this embodiment has a total calcium oxide content of 15% by mass or more, a free calcium oxide content of 0.60% by mass or more, and a chlorine content of 0.95% by mass or less.

[0027] Examples of the cement clinker include ordinary cement clinker, early strength cement clinker, moderate heat cement clinker, low heat cement clinker, and oil well cement clinker, etc. Among these, in consideration of strength characteristics and ease of availability, ordinary cement clinker and early strength cement clinker are preferably used.

[0028] The gypsum may be, for example, gypsum dihydrate, gypsum hemihydrate, anhydrous gypsum, etc. One type of gypsum may be used alone, or a combination of two or more types of gypsum may be used.

[0029] The hemihydration rate of the gypsum in the cement composition may be equivalent to the gypsum content in general Portland cement. The gypsum content in the cement composition may be, for example, 0.5 to 3.5 mass%, 1.0 to 3.0 mass%, or 1.0 to 2.5 mass%, calculated as SO3, with the total amount of the cement composition being 100 mass%.

[0030] The cement composition according to the present embodiment may have an increased hemihydration rate of gypsum because it can exhibit appropriate fluidity in a high-temperature environment by blending a predetermined admixture composition. Here, the hemihydration rate of gypsum means the mass ratio of the amount of hemihydrate gypsum to the total amount of hemihydrate gypsum and dihydrate gypsum in the cement composition. In the above cement composition, the hemihydration rate of the gypsum may be, for example, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, or 80% by mass or more. The upper limit of the hemihydration rate of the gypsum is not particularly limited, and may be 100% by mass (i.e., total amount of hemihydrate gypsum), or may be 99% by mass or less, 98% by mass or less, or 95% by mass or less. The hemihydration rate of the gypsum may be adjusted within the above range, and may be, for example, 40 to 100% by mass, or 50 to 99% by mass. In addition, when the hemihydration rate of the gypsum is less than 40% by mass, it tends to be easier to obtain stable and better fluidity. The hemihydration rate of gypsum is measured using a thermogravimetric differential thermal analyzer (TG-DTA).

[0031] The cement composition includes an admixture composition that includes biomass combustion ash. The admixture composition may further include limestone.

[0032] As the limestone, for example, powders mainly composed of calcium carbonate, such as limestone powder that is generally available on the market, and kansui stone powder, can be used. The limestone preferably includes those conforming to the minor mixing components described in JIS R 5210 "Portland cement".

[0033] The Blaine specific surface area of ​​cement is, for example, 3000 to 8000 cm 2 / g, 3000-7000cm 2 / g, 3000-6000cm 2 / g, 3000-5000cm 2 / g, or 3000-4000cm 2 / g.

[0034] In this specification, biomass combustion ash means combustion ash obtained when fuel containing at least a part of biomass fuel is burned in a process such as thermal power generation. The fuel for obtaining biomass combustion ash preferably has a high ratio of biomass fuel, more preferably contains 25 mass% or more of biomass fuel, particularly preferably contains more than 50 mass% of biomass fuel, and further preferably may be a fuel consisting of only biomass fuel. As the biomass combustion ash, combustion ash obtained by burning (single-combustion) a fuel consisting of only biomass fuel can be used, combustion ash obtained by burning (mixed-combustion) a fuel containing biomass fuel and other fuel or waste can also be used, and a mixed ash of both combustion ashes can also be used.

[0035] Examples of biomass fuels include wood chips, wood waste, wood pellets, waste wood, thinned wood, sawdust, straw, rice husks, coconut shells, corn residue, bagasse, papermaking sludge, waste pulp, waste paper, black liquor, bioethanol, bio-derived methane, livestock waste, and food processing waste. Examples of other fuels include petroleum, heavy oil, and other oils and fats. Examples of the waste materials include waste plastics, waste oil, waste tires, RPF, construction waste, construction waste soil, waste gypsum, and waste lime.

[0036] The biomass combustion ash according to the present disclosure has a total calcium oxide content of 15% by mass or more, a free calcium oxide content of 0.60% by mass or more, and a chlorine content of 0.95% by mass or less. The biomass combustion ash is suitable as a type of admixture to be added to a cement composition, and therefore can also be called biomass combustion ash for admixture.

[0037] Calcium compounds present in biomass combustion ash may exist in the form of calcium carbonate, calcium sulfate, calcium oxide (quicklime), etc., but the total calcium oxide content in this specification is a value expressed in terms of oxide as the amount of calcium present detected by fluorescent X-ray analysis of biomass combustion ash, regardless of the form of the calcium compound present.

[0038] The lower limit of the total calcium oxide content may be, for example, 20 mass% or more, 25 mass% or more, 30 mass% or more, or 35 mass% or more, and the upper limit of the total calcium oxide content may be, for example, 70.0 mass% or less, 60.0 mass% or less, 50.0 mass% or less, or 40.0 mass% or less. The total calcium oxide content may be adjusted within the above-mentioned range, and may be, for example, 15 to 70 mass% or 20 to 50.0 mass%.

[0039] The free calcium oxide content in biomass combustion ash refers to the amount of calcium present in a free state (calcium oxide as a compound), and the amount of free calcium oxide (f-CaO amount) is a value measured in accordance with the description in JCAS I-01-1997 "Method for determining free calcium oxide."

[0040] The lower limit of the free calcium oxide content may be, for example, 1.00 mass% or more, 2.10 mass% or more, 3.00 mass% or more, or 4.00 mass% or more. The upper limit of the free calcium oxide content may be, for example, 30.0 mass% or less, 20.0 mass% or less, 15.0 mass% or less, 10.0 mass% or less, or 7.0 mass% or less. The free calcium oxide content may be adjusted within the above-mentioned range, and may be, for example, 0.60 to 30.0 mass%, or 2.10 to 10.0 mass%.

[0041] The lower limit of the chlorine content (Cl content) in the biomass combustion ash may be, for example, more than 0.25% by mass. The upper limit of the chlorine content in the biomass combustion ash may be, for example, 0.80% by mass or less, 0.60% by mass or less, or 0.40% by mass or less. By including biomass combustion ash having an upper limit of the chlorine content within the above range, the resulting cement composition can have better fluidity in a high-temperature environment. The chlorine content in the biomass combustion ash may be adjusted within the above range, and may be, for example, more than 0.25% by mass and 0.95% by mass or less. The chlorine content in the biomass combustion ash can be adjusted, for example, by heating or washing the biomass combustion ash.

[0042] The lower limit of the zinc content (Zn content) in the biomass combustion ash may be, for example, 0.25 mass% or more, 0.50 mass% or more, or 1.0 mass% or more. The upper limit of the zinc content in the biomass combustion ash may be, for example, 20.00 mass% or less, 10.00 mass% or less, or 5.00 mass% or less. The zinc content in the biomass combustion ash may be adjusted within the above-mentioned range, and may be, for example, 0.25 to 20.00 mass% or 0.25 to 5.00 mass%.

[0043] As the biomass combustion ash, from the viewpoint of strength development, it is preferable to use a powder having a low silicon dioxide content (SiO2 content). The upper limit of the SiO2 content of the biomass combustion ash may be, for example, 50.0 mass% or less, 45.0 mass% or less, 40.0 mass% or less, 30.0 mass% or less, or 20.0 mass% or less. As the biomass combustion ash, from the viewpoint of effective utilization of waste and by-products, it is preferable to use a powder having a high silicon dioxide content (SiO2 content). The lower limit of the SiO2 content of the biomass combustion ash may be, for example, 1.0 mass% or more, 5.0 mass% or more, or 10.0 mass% or more.

[0044] As the biomass combustion ash, from the viewpoint of strength development, it is preferable to use a powder having a low aluminum oxide content (Al2O3 content). The upper limit of the Al2O3 content of the biomass combustion ash may be, for example, 20.0 mass% or less, 14.0 mass% or less, 11.0 mass% or less, or 8.0 mass% or less. As the biomass combustion ash, from the viewpoint of effective utilization of waste and by-products, it is preferable to use a powder having a high aluminum oxide content (Al2O3 content). The lower limit of the Al2O3 content in the biomass combustion ash may be, for example, 1.0 mass% or more, 3.0 mass% or more, 6.0 mass% or more, or 7.0 mass% or more.

[0045] As the biomass combustion ash, from the viewpoint of strength development, it is preferable to use a powder having a low sulfur trioxide content (SO3 content). The upper limit of the SO3 content of the biomass combustion ash may be, for example, 25.0 mass% or less, 20.0 mass% or less, 15.0 mass% or less, or 12.0 mass% or less. As the biomass combustion ash, from the viewpoint of effective utilization of waste and by-products, it is preferable to use a powder having a high SO3 content (SO3 content). The lower limit of the SO3 content in the biomass combustion ash may be, for example, 0.1 mass% or more, 1.0 mass% or more, 3.0 mass% or more, or 5.0 mass% or more.

[0046] The upper limit of the R2O content of the biomass combustion ash may be, for example, 5.0% by mass or less, 3.0% by mass or less, 2.0% by mass or less, or 1.5% by mass or less. From the viewpoint of effective utilization of waste and by-products, it is preferable to use a powder having a high R2O content (R2O content) as the biomass combustion ash. The lower limit of the R2O content in the biomass combustion ash may be, for example, 0.1% by mass or more, 0.3% by mass or more, 0.5% by mass or more, or 1.0% by mass or more.

[0047] The biomass combustion ash may be used after adjusting the particle size by crushing or the like. The lower limit of the Blaine specific surface area of ​​the biomass combustion ash is, for example, 3000 cm 2 / g or more, 6800cm 2 / g or more, 7000cm 2 / g or more, 8000cm 2 / g or more, 9000cm 2 / g or more, or 10,000 cm 2 / g or more. By setting the lower limit of the Blaine specific surface area within the above range, the strength of the cement composition when hardened can be further improved. The upper limit of the Blaine specific surface area of ​​the biomass combustion ash is, for example, 50,000 cm 2 / g or less, 40000cm 2 / g or less, 30000cm 2 / g or less, or 20000cm 2 / g or less. When the upper limit of the Blaine specific surface area is within the above range, deterioration in handleability is suppressed, and the production of the cement composition can be more easily carried out. The Blaine specific surface area of ​​the biomass combustion ash may be adjusted within the above range, for example, 3000 to 50000 cm. 2 / g, or 9000 to 20000 cm 2 / g.

[0048] The content of the admixture composition is more than 5.0% by mass and not more than 20.0% by mass based on the total amount of the cement composition. The lower limit of the content of the admixture composition may be, for example, 6.0% by mass or more, 7.0% by mass or more, or 8.0% by mass or more based on the total amount of the cement composition. When the lower limit of the content of the admixture composition is within the above range, the cement composition can be produced with a reduced environmental load. The upper limit of the content of the admixture composition may be, for example, 15.0% by mass or less, 12.0% by mass or less, or 10.0% by mass or less based on the total amount of the cement composition. When the upper limit of the content of the admixture composition is within the above range, the strength of the resulting cement composition when hardened can be further improved.

[0049] When the admixture composition further contains limestone, the content of the biomass combustion ash may be 0.1 to 55.0% by mass based on the total amount of the limestone and the biomass combustion ash. The lower limit of the content of the biomass combustion ash may be, for example, 0.5% by mass or more, 1.0% by mass or more, 3.0% by mass or more, 5.0% by mass or more, 10.0% by mass or more, or 15.0% by mass or more based on the total amount of the limestone and the biomass combustion ash. The content of the biomass combustion ash may be, for example, 50.0% by mass or less, 40.0% by mass or less, or 30.0% by mass or less based on the total amount of the limestone and the biomass combustion ash.

[0050] The mineral composition and chemical composition of the cement clinker according to the Bogue formula may be, for example, that the C3S content is 40.0 to 70.0 mass%, the C2S content is 5.0 to 40.0 mass%, the C3A content is 7.0 to 13.0 mass%, and the C4AF content is 7.0 to 13.0 mass%.

[0051] The C3S content of the cement clinker may be, for example, 50.0 to 55.0 mass%. The C2S content of the cement clinker may be, for example, 15.0 to 25.0 mass%. The C3A content of the cement clinker may be, for example, more than 10.5 mass% and not more than 11.5 mass%. The C3AF content of the cement clinker may be, for example, 9.0 to 10.0 mass%.

[0052] The amount of SO3 in the cement composition may be, for example, 1.0 to 3.5 mass %, 1.2 to 3.0 mass %, or 1.5 to 2.5 mass %.

[0053] The cement composition may further contain an admixture in addition to the cement clinker, gypsum, and admixture composition. Examples of the admixture include AE ​​agents, water reducing agents, AE water reducing agents, high-performance water reducing agents, high-performance AE water reducing agents, superplasticizers, antifoaming agents, shrinkage reducing agents, setting accelerators, setting retarders, and thickeners. The cement composition preferably contains at least one admixture selected from the group consisting of water reducing agents, AE water reducing agents, high-performance water reducing agents, high-performance AE water reducing agents, and superplasticizers among the above-mentioned admixtures. The admixture preferably contains a polycarboxylic acid compound, and more preferably contains a polycarboxylic acid compound and a phosphonic acid compound. The content of the admixture may be, for example, 0.01 to 3 parts by mass with respect to 100 parts by mass of the above-mentioned cement composition.

[0054] The above-mentioned cement composition can be produced, for example, by the following production method. One embodiment of the production method of the cement composition includes a mixing step of mixing raw materials including cement clinker, gypsum, and the above-mentioned admixture composition.

[0055] The mixing step is a step of mixing raw materials including cement clinker, gypsum, and the admixture composition so that the content of the admixture composition is more than 5.0 mass % and not more than 20.0 mass %.

[0056] In the mixing step, in addition to mixing each main component, each main component may be crushed, and the order of mixing and crushing is not particularly limited. That is, each main component may be mixed and then crushed, each main component may be crushed and then mixed, or each main component may be mixed and crushed simultaneously. The mixing of each main component in the mixing step may be performed using a mixer such as a pan mixer, a tilting mixer, or a ribbon mixer, or may be mixed and crushed using a crusher such as a ball mill or a vertical roller mill, or a roller press, or each main component may be crushed and then mixed using a mixer such as a mechanical mixer.

[0057] In the method for producing the cement composition, it is preferable to mix cement clinker, gypsum, and the admixture composition. However, instead of the cement clinker and gypsum, a cement in which cement clinker, gypsum, and limestone are mixed in advance may be used, and the admixture composition may be mixed with the cement.

[0058] In the case where the admixture composition further contains limestone, when the admixture composition is mixed with cement in which limestone has been mixed beforehand, the content of biomass combustion ash relative to the total amount of limestone mixed in the cement and the amount of limestone contained in the admixture composition is adjusted so as to satisfy the above-mentioned relationship, thereby making it possible to obtain an effect equivalent to that obtained when mixing cement clinker, gypsum, and the admixture composition.

[0059] When there are multiple types of raw materials to be used as an admixture composition, they may be mixed into the admixture composition and then mixed and crushed with each main component, or the above-mentioned mixing and crushing may be applied by treating each raw material as equivalent to the main component without previously mixing them into an admixture composition.

[0060] The mixed cement composition produced by the above-mentioned production method may be mixed with fine aggregate, coarse aggregate, water, admixtures, etc., and used as mortar.

[0061] The fine aggregate may be one specified in JIS A 5005:2020 "Crushable stone and crushed sand for concrete". Examples of fine aggregate include river sand, land sand, sea sand, crushed sand, silica sand, copper slag fine aggregate, and electric furnace oxidized slag fine aggregate. When using fine aggregate, the amount of fine aggregate may be, for example, 50 to 500 parts by mass, 100 to 300 parts by mass, or 200 to 250 parts by mass relative to 100 parts by mass of the above-mentioned mixed cement composition.

[0062] The coarse aggregate may be one specified in JIS A 5005:2020 "Crushable stone and crushed sand for concrete". Examples of the coarse aggregate include gravel and crushed stone. When using coarse aggregate, the amount of the coarse aggregate may be, for example, 50 to 500 parts by mass, 100 to 300 parts by mass, or 200 to 250 parts by mass relative to 100 parts by mass of the above-mentioned mixed cement composition.

[0063] Fine aggregate and coarse aggregate can be used in combination. In this case, the total amount of fine aggregate and coarse aggregate used may be 100 to 300 parts by mass, or 200 to 250 parts by mass, per 100 parts by mass of the above-mentioned mixed cement composition.

[0064] Examples of water include tap water, distilled water, deionized water, etc. The amount of water used may be 20 to 100 parts by mass, or 40 to 70 parts by mass, based on 100 parts by mass of the above-mentioned mixed cement composition.

[0065] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the descriptions of the above-described embodiments can be mutually applied. EXAMPLES

[0066] The present disclosure will be described in more detail below with reference to examples, comparative examples, and reference examples. However, the present disclosure is not limited to the following examples.

[0067] [Raw materials for cement composition] The following materials were used as raw materials for the cement composition.

[0068] (Cement clinker) The cement clinker used was ordinary Portland cement clinker whose mineral composition according to the Bogue formula is as shown in Table 1 below. The chemical components of the cement used in the calculations according to the Bogue formula were measured in accordance with the method described in JIS R 5204 "Fluorescent X-ray analysis of cement."

[0069] [Table 1]

[0070] (plaster) The gypsum used was one that satisfied the requirements set forth in JIS R 9151:2009 "Natural gypsum for cement."

[0071] (mixed material) The admixtures used were limestone, biomass combustion ash, and coal ash, which will be described later. The properties of each admixture (total calcium oxide amount, free calcium oxide amount, chemical composition, and Blaine specific surface area) are shown in Table 2.

[0072] ·Limestone The limestone (CC) used had a calcium carbonate content of 90 mass% or more and an aluminum oxide content of 1.0 mass% or less, and satisfied the requirements for minor mixed components described in JIS R 5210:2009 "Portland cement."

[0073] Biomass combustion ash Biomass combustion ash (BA) has a Blaine specific surface area of ​​6520 to 11000 cm 2 Biomass combustion ashes BA1 to BA6, each having a carbon content of 1.0 to 1.5 g, were used. BA2 was biomass combustion ash obtained by pulverizing BA1 in a ball mill.

[0074] ·Coal ash The coal ash (FA) used was coal ash (FA1, FA2) that conforms to JIS A 6201:2015 Fly Ash for Concrete Type II. FA2 is coal ash with calcium oxide (quicklime) added to FA1. The quicklime used was obtained by igniting reagent calcium carbonate at 950℃ until it reached a constant weight.

[0075] (Admixture) ·High-performance water reducer As the high-performance water-reducing agent, "OPTIMA SL 183" (product name) from CHRYSO was used. "OPTIMA SL 183" is a high-performance water-reducing agent that contains a polycarboxylic acid compound and a phosphonic acid compound.

[0076] (Examples 1 to 2, Comparative Examples 1 to 8, and Reference Examples 1 to 3) Cement clinker, gypsum, and various admixtures (limestone, biomass combustion ash, coal ash) were mixed and pulverized in the amounts (mass %) shown in Table 2 to prepare a cement composition.

[0077] The amount of gypsum (SO3 equivalent value), the amount of limestone added, the amount of SO3, and the hemihydration rate of gypsum for the cement composition are shown in Table 2. The amount of SO3 in cement means a chemical analysis value of cement measured according to the method described in JIS R 5204 "Fluorescent X-ray analysis method for cement." The hemihydration rate of gypsum was measured with a thermogravimetric differential thermal analyzer (TG-DTA).

[0078] <Measurement of properties of admixture> For each admixture in Table 2, the total calcium oxide content, free calcium oxide content, chemical composition, and Blaine specific surface area were determined as follows. The chemical composition of the admixture was quantified by the fundamental parameter method using a scanning X-ray fluorescence device. The amount of free calcium oxide (f-CaO amount) was measured in accordance with the description in JCAS I-01-1997 "Method for quantification of free calcium oxide," and the Blaine specific surface area was measured in accordance with the description in JIS R 5201:2015 "Physical measurement method for cement." For the X-ray fluorescence analysis, Rigaku Corporation's "ZSX-100e" (product name) was used.

[0079] <Measurement of shear stress> Shear stress was measured using the various cement compositions prepared in Examples 1 and 2, Comparative Examples 1 to 8, and Reference Examples 1 to 3. In addition, assuming use in a high-temperature environment, the fluidity was evaluated under the condition of 35°C.

[0080] Specifically, a paste was prepared and mixed by adding an aqueous solution of a high-performance water reducing agent so that the content of the high-performance water reducing agent was 1.0 part by mass per 100 parts by mass of the cement composition. At this time, the amount of water was adjusted to 34 parts by mass per 100 parts by mass of the cement composition. Mixing was performed in a thermostatic chamber at 35°C using a chemical mixer at 600 rpm for 3 minutes. After mixing, the paste was immediately placed in a measurement container, and the shear stress immediately after mixing was measured using a rheometer. Thereafter, the paste was left to stand in a thermostatic chamber at 35°C while preventing evaporation of water, and cured. After 120 minutes had passed since the start of curing, the paste was mixed again, and then placed in a measurement container again, and the shear stress at 120 minutes was measured using a rheometer.

[0081] The shear stress was measured using a coaxial double cylinder rheometer (Anton Paar, product name: MCR101) at a shear rate of 10 -5 ~10 3 s -1 More specifically, the range of change in shear rate was divided into 36 points on a logarithmic axis, and at each of the 36 points, shear was applied for 5 seconds at the shear rate at that point to measure the shear stress. -5 From 10 3 s -1 The shear rate was then increased to 1000 s (ascending curve). The shear rate was then gradually decreased in the same manner (descending curve), and the shear stress was measured. -1 Shear stress value (0.1s -1 The fluidity was evaluated immediately after mixing and 120 minutes after mixing. The temperature inside the measurement container was kept at 35°C during the measurement of fluidity. When the shear stress was 0.15 to 10.0 Pa, the fluidity was evaluated as excellent.

[0082] [Table 2]

[0083] Examples 1 and 2 shown in Table 2 are experimental examples in which part of the limestone in Comparative Example 1 was replaced with the specified biomass combustion ash according to the present disclosure. As shown in Table 2, it can be confirmed that the cement compositions of Examples 1 and 2 suppress the decrease in shear stress at 120 minutes of age. Even when the hemihydration rate of gypsum is high, which is a major problem of fluidity decrease over time in a high temperature environment, the above-mentioned effect can be obtained, and it is considered that the same effect can be obtained even when the hemihydration rate of gypsum is low. In addition, from a comparison of the results of Example 1 and Example 2, it can also be confirmed that the effect can be increased by increasing the proportion of biomass combustion ash in the admixture.

[0084] In order to confirm that a high hemihydration rate of gypsum leads to a significant problem of decreased fluidity over time in a high-temperature environment, Reference Examples 1 and 2 were shown. Comparing the results of shear stress in Reference Example 1, in which the hemihydration rate of gypsum is less than 40% by mass, with Reference Example 2, in which the hemihydration rate of gypsum is 40% by mass or more, it can be seen that when the hemihydration rate of gypsum is high, the decrease in shear stress after a long period of time in a high-temperature environment is significant, which can cause problems in terms of maintaining fluidity.

[0085] In Examples 1-2, Comparative Examples 1-8, and Reference Example 3, the hemihydration rate of gypsum was set to 81% by mass, assuming that the shear stress would decrease significantly after a long period of time in a high-temperature environment and that the use would be under conditions where problems related to fluidity would be easily manifested. Reference Example 3 is an experimental example in which 3.9% by mass of limestone was added as an admixture and generally used ordinary Portland cement was assumed. Although the shear stress immediately after mixing was relatively excellent at 2.16 Pa, it was confirmed that the shear stress at 120 minutes after 120 minutes had passed was significantly reduced to 0.09 Pa. Comparative Example 1 is an experimental example in which the amount of admixture was increased and the entire amount was limestone, and in this case as well, it was confirmed that the shear stress at 120 minutes was significantly reduced, as in Reference Example 3.

[0086] Next, Comparative Examples 2 to 6 are examples using biomass combustion ash different from Examples 1 and 2, and Comparative Examples 7 and 8 are examples using coal ash as an admixture. As shown in Table 2, it was confirmed that even the cement compositions of Comparative Examples 2 to 8 showed a large decrease in shear stress at 120 minutes under high temperature conditions.

[0087] Coal ash was used as an admixture in Comparative Examples 7 and 8. The coal ash (FA2) used in Comparative Example 8 was obtained by adding quicklime to the coal ash (FA1) used in Comparative Example 7 to increase the amount of free calcium oxide. Comparative Examples 7 and 8 confirmed that fluidity in a high-temperature environment cannot be improved simply by compensating for the amount of free calcium oxide. [Industrial Applicability]

[0088] According to the present disclosure, it is possible to provide an admixture composition capable of imparting fluidity to a cement composition in a high-temperature environment. According to the present disclosure, it is also possible to provide a cement composition that contains the above-mentioned admixture composition, contributes to reducing environmental load, and exhibits appropriate fluidity in a high-temperature environment, and a method for producing the same.

Claims

1. An admixture composition for use in producing a cement composition, comprising: the admixture composition comprises biomass combustion ash; The biomass combustion ash has a total calcium oxide content of 15% by mass or more, a free calcium oxide content of 0.60% by mass or more, and a chlorine content of 0.95% by mass or less.

2. 2. The admixture composition of claim 1, wherein the zinc content in the biomass combustion ash is 0.25% by mass or more.

3. The Blaine specific surface area of ​​the biomass combustion ash is 7000 cm 2 3. The admixture composition of claim 1, wherein the SiO2 content is 1 / g or more.

4. Further comprising limestone, The content of the biomass combustion ash is 0.1 to 55.0 mass% based on the total amount of the biomass combustion ash and the limestone. The admixture composition according to any one of claims 1 to 3.

5. A method for producing a mixture comprising the steps of: cement clinker, gypsum, and the admixture composition according to any one of claims 1 to 4; The content of the admixture composition is more than 5.0 mass% and not more than 20.0 mass%.

6. The cement composition according to claim 5, wherein the hemihydration rate of the gypsum is 40 to 100 mass%.

7. The cement clinker is C 3 The amount of S is 40.0 to 70.0 mass%, and C 2 The amount of S is 5.0 to 40.0 mass%, and C 3 The amount of A is 7.0 to 13.0 mass%, and C 4 The cement composition according to claim 5 or 6, wherein the AF content is 7.0 to 13.0 mass%.

8. The SO of the cement composition 3 A cement composition according to any one of claims 5 to 7, wherein the amount is from 1.0 to 3.5% by weight.

9. The cement composition according to any one of claims 5 to 8, comprising at least one admixture selected from the group consisting of a water reducing agent, an air-entraining water reducing agent, a high-performance water reducing agent, a high-performance air-entraining water reducing agent, and a fluidizing agent.

10. The cement composition of claim 9, wherein the admixture comprises a polycarboxylic acid compound.

11. A method for producing a cement composition, comprising: a mixing step of mixing raw materials including cement clinker, gypsum, and the admixture composition according to any one of claims 1 to 4 such that the content of the admixture composition is more than 5.0 mass% and not more than 20.0 mass%.

Citation Information

Patent Citations

  • Mixing material for cement and cement composition

    JP1995069694A

  • Papermaking-sludge-ash-containing granule and method for manufacturing the same

    JP2005103464A

  • Hydraulic composition, hardened body using the same, and method for producing the hardened body

    JP2005255473A

  • Plasticizing additive for mortar and method of producing mortar using the same

    JP2006069854A

  • Soil improving and solidifying material

    JP2006241232A